2010
DOI: 10.1097/rli.0b013e3181e45578
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of the Cardiac Venous System and Magnetic Resonance-Guided Intubation of the Coronary Sinus in Swine

Abstract: MR-visualization and MR-guided intubation of the coronary sinus and its side branches is feasible. The feasibility of MR-guided intubation of the CVS might have relevance for procedures like cardiac resynchronization therapy and percutaneous transcatheter mitral annuloplasty, requiring improved 3-dimensional knowledge about cardiac vein anatomy in the near future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…However, recent developments in this field have been published [7] and aortic stenting, renal stenting and cava filter placement guided exclusively by MR using a MR-compatible guide wire have been safely and effectively performed in swine models [8,9]. Also, the feasibility of MR-visualization and MR-guided intubation of the coronary sinus has been demonstrated recently in an animal study [10], which might have relevance in the near future for procedures that require improved three-dimensional knowledge about the cardiac vein anatomy, such as cardiac resynchronization therapy and percutaneous transcatheter mitral annuloplasty. In another animal study, MR imaging roadmaps of cardiac structures were obtained from miniature swine with spontaneous VSDs and registered with live X-ray using external fiducial markers [11].…”
Section: Magnetic Resonance-guided Percutaneous Interventionsmentioning
confidence: 99%
“…However, recent developments in this field have been published [7] and aortic stenting, renal stenting and cava filter placement guided exclusively by MR using a MR-compatible guide wire have been safely and effectively performed in swine models [8,9]. Also, the feasibility of MR-visualization and MR-guided intubation of the coronary sinus has been demonstrated recently in an animal study [10], which might have relevance in the near future for procedures that require improved three-dimensional knowledge about the cardiac vein anatomy, such as cardiac resynchronization therapy and percutaneous transcatheter mitral annuloplasty. In another animal study, MR imaging roadmaps of cardiac structures were obtained from miniature swine with spontaneous VSDs and registered with live X-ray using external fiducial markers [11].…”
Section: Magnetic Resonance-guided Percutaneous Interventionsmentioning
confidence: 99%
“…However, the materials selection indicates dynamic development promising rapid progress. Larger arterial and venous vessels can be safely and gently probed with the currently available wires [54].…”
Section: Instruments and New Operating Concepts For Vascular Intervenmentioning
confidence: 99%
“…Therefore, the catheters, and in particular the coronary sinus catheter, were initially inserted with fluoroscopic guidance to be able to spend more time on the ablation procedure. A previous study, however, demonstrated that MR imaging-guided intubation of the coronary sinus is reproducibly feasible in swine (18). The authors visualized the anatomy of the coronary sinus by using a three-dimensional steady-state free precession whole-heart sequence prior to real-time steady-state free precession guidance.…”
Section: Ep Ablation Studiesmentioning
confidence: 99%